2020
DOI: 10.5194/esd-11-709-2020
|View full text |Cite
|
Sign up to set email alerts
|

What could we learn about climate sensitivity from variability in the surface temperature record?

Abstract: Abstract. We examine what can be learnt about climate sensitivity from variability in the surface air temperature record over the instrumental period, from around 1880 to the present. While many previous studies have used trends in observational time series to constrain equilibrium climate sensitivity, it has also been argued that temporal variability may also be a powerful constraint. We explore this question in the context of a simple widely used energy balance model of the climate system. We consider two re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The results may also be sensitive to the metric and the set of models used; an earlier study using a similar idea found no constraint (Masson and Knutti, 2013), and in some cases reversed signs of correlations between CMIP and PPEs, thus questioning the robustness of the approach. Other studies (Annan et al, 2020) have performed objective Bayesian constraint of ECS through climate variability in simple models, finding a wider constrained range wider than suggested by Cox 2018. As such, a confirmation of the strength of the Cox 2018 610 relationship under CMIP6 would provide valuable additional data on its robustness.…”
Section: Constraining Climate Sensitivity With Fluctuation-dissipatiomentioning
confidence: 79%
“…The results may also be sensitive to the metric and the set of models used; an earlier study using a similar idea found no constraint (Masson and Knutti, 2013), and in some cases reversed signs of correlations between CMIP and PPEs, thus questioning the robustness of the approach. Other studies (Annan et al, 2020) have performed objective Bayesian constraint of ECS through climate variability in simple models, finding a wider constrained range wider than suggested by Cox 2018. As such, a confirmation of the strength of the Cox 2018 610 relationship under CMIP6 would provide valuable additional data on its robustness.…”
Section: Constraining Climate Sensitivity With Fluctuation-dissipatiomentioning
confidence: 79%
“…From a last-millennium perspective, we can effectively address significant questions posed by the research community regarding prior endeavors to constrain ECS via temperature variability. Notably, it was previously suggested that the instrumental record is too brief to accurately measure global temperature variability for the purposes of constraining ECS and cannot be used alone to constrain climate sensitivity (Annan et al, 2020). We find that while the observed estimate of interannual temperature variability is weakly sensitive to the period of analysis (Table S3 in Supporting Information S1), individual GCMs can exhibit meaningful differences in estimates of ψ produced when calculated over the past millennium (Figure S2 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%
“…Our constraints, which imply an ECS between 2.5 ± 0.8 K (for ψ ) and 2.7 ± 0.8 K (for σ b ), are slightly lower than the IPCC's central estimate of 3K, but substantially overlap with the IPCC's likely range. The ability of temperature variability to constrain ECS on its own has been shown to be limited, especially in cases where climate sensitivity is greater than 2.5 K (Annan et al., 2020). Therefore, instead of viewing our study as fully capable of constraining ECS on its own, we contend that our estimates and their associated uncertainties should be regarded as an additional source of knowledge within the existing body of work to generate the most accurate ECS estimate (Sanderson et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results may also be sensitive to the metric and the set of models used; an earlier study using a similar idea found no constraint (Masson and Knutti, 2013), and in some cases reversed signs of correlations between CMIP and PPEs, thus questioning the robustness of the approach. Other studies (Annan et al, 2020)…”
Section: Constraining Climate Sensitivity With Fluctuation-dissipation Relationshipsmentioning
confidence: 99%